Structural Functional Framework In Ahmad Al-Mutawakkil's An-Nachw Al-Wazhafi - Muhammad Habibie Alfath; Muhamad Saiful Mukminin; Tareq Alfraidi (Jurnal Al-Maqoyis, 2026)
The development of modern Arabic grammar no longer focuses solely on formal structure. Grammar is understood as a system that integrates linguistic structure and communicative function in response to contemporary communicative needs and social contexts. This study analyzes Ahmad Al-Mutawakkilâ€™s Functional Grammar through Talcott Parsonsâ€™ structural-functional framework, focusing on how linguistic structures fulfil communicative functions in the Arabic language system. Using content analysis, it examines Al-LisÄniyyÄt Al-WazhÄ«fiyyah: Madkhal Nazhariyy alongside Abdullah et al. (2024). The findings reveal that Al-Mutawakkilâ€™s grammar integrates Parsonsâ€™ AGIL framework: Adaptation through structural flexibility for diverse contexts; Goal Attainment via organizing semantic, structural, and pragmatic levels toward communication goals; Integration through cohesion among levels, theory-practice linkage, and synthesis of classical and modern thought; and Latency through renewal, preservation of tradition, and contextual applicability. The merging of morphology and syntax within three analytical levels corrects classical linguistic fragmentation, centering communicative function as the primary organizing principle. Diverging from Dhaifâ€™s pedagogical simplification and Hallidayâ€™s functional reconstruction, Al-Mutawakkil revitalizes Arabic grammar for contemporary use, uniting linguistic form, communicative purpose, and social meaning in a coherent theoretical synthesis.